PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA SERTA KEMAMPUAN PEMECAHAN MASALAH MELALUI MODEL PROBLEM BASED LEARNING PADA KONSEP CAHAYA DI KELAS VIII.E SMPN 6 KOTA BENGKULU - Elda Lestari Baksir; Afrizal Mayub; Desy Hanisa Putri (Kumparan Fisika, 2017)
This study aims to improve the activity, student learning outcomes and problem-solving skills on the concept of light performed in four cycles. Subjects in this study were all students of class VIII.E which amounted to 21 people. The instruments used are observation sheets for teacher and student activities, affective learning, psychomotor and cognitive test sheets and problem solving skills. The result of the research shows that student learning activity in cycle I with average score of 31,5 categories is enough, cycle II is 34 good category, cycle III is 38 good category and IV cycle is 40 good category. The result of cognitive learning obtained by average of cycle I is 53,3 less category, cycle II equal to 65,71 category enough, cycle III equal to 80 category good and cycle IV equal to 90,48 good category. Psychomotor learning results obtained in the first cycle of 8.64 categories enough, cycle II for 10 categories both, cycle III of 10.48 good category and IV cycle equal 11.04 good category, and affective learning results obtained cycle I of 12.19 Category enough, cycle II 13,74 category enough, cycle III equal to 14,83 good category, cycle IV equal to 16,17 in good category. As well as the results of problem-solving abilities. In cycle I the problem solving ability of students with percentage of 56% less category, increase in cycle II problem solving ability of student with percentage of 72% category enough, then increase in cycle III with percentage of 76% good and in cycle IV increase again with percentage 79% good. Based on the results of research can be concluded that the application of problem-based learning model can boost the activity and student learning outcomes and problem-solving skills.